2019
DOI: 10.1002/er.5006
|View full text |Cite
|
Sign up to set email alerts
|

A multiperiod multiobjective framework for the synthesis of trigeneration systems in tertiary sector buildings

Abstract: This paper develops a multiperiod multiobjective optimization procedure to determine the optimal configuration and operational strategy of a trigeneration system assisted with solar-based technologies and thermal energy storage. The optimization model, formulated as mixed integer linear programming problem, incorporates dynamic operating conditions through time-dependent local climatic data, energy resources, energy demands, electricity prices, and electricity CO 2 emission factors. The methodology is applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…One of the decisive factors for this condition is the challenge of carrying out a robust and comprehensive synthesis procedure that must consider the multi-faceted nature of polygeneration systems for buildings [9,10]: multiple energy resources (renewable and nonrenewable), multiple energy products (electricity, steam, hot water, chilled water), multiple technology options (generation, transformation and storage technologies), and multiple operation periods (hourly and seasonal variations in energy resources, energy demands and climatic conditions, and temporal variations in energy prices).…”
Section: The Synthesis Of Polygeneration Systems For Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the decisive factors for this condition is the challenge of carrying out a robust and comprehensive synthesis procedure that must consider the multi-faceted nature of polygeneration systems for buildings [9,10]: multiple energy resources (renewable and nonrenewable), multiple energy products (electricity, steam, hot water, chilled water), multiple technology options (generation, transformation and storage technologies), and multiple operation periods (hourly and seasonal variations in energy resources, energy demands and climatic conditions, and temporal variations in energy prices).…”
Section: The Synthesis Of Polygeneration Systems For Buildingsmentioning
confidence: 99%
“…Carvalho et al [38] proposed a multicriteria synthesis of CCHP systems for a Spanish hospital; all waste heat from the ICE was now recovered as hot water at the same temperature level, while the waste heat from the GT was used to produce both steam and hot water. Pina et al [9] carried out a MOO procedure of CCHP systems for a residential building in Spain; it was assumed that the ICE produced high-and low-temperature heat to drive the absorption chiller and to cover the heating demands, respectively; also, solar thermal collectors operated at high-temperature in the summer and low-temperature in the winter.…”
Section: The Issue Of Thermal Integration In Energy Systems For Buildingsmentioning
confidence: 99%
“…and obtained considerable cost reduction (about 20%) and CO 2 emissions reduction (about 40%) compared to conventional separate heat and power production. Finally, Pina et al 22 developed a multiobjective framework for the synthesis of polygeneration systems and applied to a residential multifamily building consisting of 100 dwellings in Spain, and reached also the conclusion of the important role of HP in the reduction of CO 2 emissions, as well as the economic interest of installing PV at the expense of CM when additional CO 2 reduction was required. Moreover, the installation of TSR was also preferred to TSQ.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Another important aspect to be considered in the design of affordable polygeneration systems for residential buildings is the connection with the electrical grid and the possibility of purchasing and/or selling electricity to it, which provides reliability and security to the building energy supply as well as flexibility and economic benefits. 21,22 However, the feasibility of polygeneration systems depends, among others, on the applied energy policies and legal framework. For instance, previous studies have demonstrated how some policies could promote or limit the installation of specific technologies such as cogeneration 23 or photovoltaic technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation